ANALISIS PERGESERAN MAKNA TRADISI TARI NGEBENG DI DESA RAMBUTAN MASAM KABUPATEN BATANG HARI - Permatasari, Indah; Dewi, Nurmalia; Khotimah, Khusnul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the shift in meaning occurring within the Tari Ngebeng tradition in Rambutan Masam Village. A tradition that originally served a ritualistic function in agricultural contexts has undergone changes in form and meaning over time. Consequently, it is crucial to uncover how the original meaning of Tari Ngebeng has shifted and the factors influencing these changes through the ages. The informants in this study include traditional Ketua Adat and the village community. This study employs a descriptive qualitative approach. Data collection techniques include observation, interviews, and documentation, while data analysis follows the stages of data collection, data reduction, and data presentation. The results indicate a significant shift in the meaning of the Tari Ngebeng tradition in Rambutan Masam Village, Batanghari Regency. Historically, Tari Ngebeng was an integral part of community rituals related to agricultural activities, specifically as an expression of gratitude for the rice harvest and a means of strengthening social cohesion. The tradition possessed strong sacred, religious, and social values. However, in the modern era, Tari Ngebeng is more frequently performed as entertainment, cultural performances for welcoming guests, cultural festivals, and government events. This shift is evident in the changes in function, execution procedures, community participation, and the interpretation of cultural symbols embedded within the dance.